Atypical presentation of craniofacial fibrous dysplasia in an adult - Padma B Prabhu; Swetha Mediyala Hanumappa; Kuzupally Vallon Raju (Wolters Kluwer Medknow Publications, 2016)
Fibrous dysplasia is a sporadic fibroosseous anomaly affecting the skeletal system. Craniofacial synostosis is one of its subtypes with ocular complications. We report a case of craniofacial fibrous dysplasia in a 44-year-old lady who presented with complaints of recent onset of blurring of vision in both eyes. She gave a history of swelling in the medial aspect of left eye since childhood with minimal increase in size with age. A bony swelling was seen along the medial wall of left orbit associated with deviated nasal septum to the right. She had best corrected visual acuity (BCVA) of 20/20 in eyes, normal color vision, visual fields and fundus findings. Her computed tomography (CT) scan was suggestive of fibrous dysplasia involving multiple bones (frontal, sphenoid, ethmoid, maxillary, and pterygoid bones) bilaterally. Visual evoked potential was abnormal bilaterally.